The easiest way to do this would be to put the equation for y in terms of x.
We have x+y = 6
subtracting x from both sides gives y = 6 - x
This is of the form y = ax + b where b is 6 and a is minus 1.
So the graph will be a line, with gradient minus 1, that crosses the y axis at y=6
3
X equals 6 ..
The graph is a circle with a radius of 6, centered at the origin
7
x=6=x=5+x=13+x=20 x cannot = x+5. This question has no answer.
The graph is a circle with a radius of 6, centered at the origin.
y=x+1 there for answer is 2
Graph and Table: http://i50.tinypic.com/szhr4k.png
First of all, if 'x' is 3, then 'x' doesn't equal -3x+3 . You must mean y = -3x + 3.If x=3, then (-3x + 3) = -6 .The graph is the point (3, -6) .
y equals x-4 plus 2 is the same as y = x-2. You just translate the graph of y=x, 2 units to the right, OR 2 down.
3
To graph them, you need to put them into the formula y=mx+b. If x+y=8 subtract x to get y=-x+8. 8 is the y-intercept and your line should be heading downward from left to right.
(-1,0)
X equals 6 ..
The graph is a circle with a radius of 6, centered at the origin
7
down